Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M.; Fagnano, M.; Amoriello, T.; Badiani, M.; Ballarin-Denti, A.; Buffoni, A.; Bussotti, F.; Castagna, A.; Cieslik, S.; Costantini, A.; De Marco, A.; Gerosa, G.; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
The following values have no corresponding Zotero field: accession-num: 16889878
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux

A field system to deliver desired O-3 concentrations in leaf-level gas exchange measurements: Results for Holm oak near a CO2 spring - Grulke, N. E.; Paoletti, E. (PHYTON-ANNALES REI BOTANICAE, 2005)
Conventional gas exchange systems adsorb ozone (O-3) despite attempts to saturate the system prior to measurements. A steady-state, open photosynthetic system was designed and used in the field to supply a small leaf cuvette with conditioned air stream (growth CO2 concentrations, humidified, cooled) and augmented with either background or elevated O-3. Two innovations led to success: 1) supplying the cuvette with cooled air instead of Peltier cooling within the cuvette; and 2) using a custom-designed, low flow (capable of 100 seem), fast response (20 S) O-3 monitor. We tested whether elevated CO2 would alter stomatal response to short term, steady state elevated O-3. Holm oak (Quercus ilex L., Fagaceae), an evergreen broadleaf tree growing near a geothermal CO2 vent, has been exposed over its lifetime to a gradient of CO2 concentrations. We chose trees in areas averaging 450 mu l 1(-1) (low background CO2) and 1500 mu l 1(-1) (super-elevated CO2). Background O-3 exposure at this site is moderate (10 am to 5 pm averages of 62 nl 1(-1) in June). We measured gas exchange at the growth CO2 levels, and at ambient O-3 or 1.7x ambient O-3 concentrations. At low background CO2, short term elevated O-3 depressed foliar transpiration. Because there was little concurrent change in net assimilation, instantaneous transpiration efficiency was increased. At super-elevated CO2, short term elevated O-3 did not affect foliar transpiration. Because there was a concurrent decrease in net assimilation, instantaneous transpiration efficiency was decreased at elevated CO2 and O-3.
The following values have no corresponding Zotero field: pub-location: WIENER STRASSE 21-23, A-3580 HORN, AUSTRIA publisher: FERDINAND BERGER SOEHNE
Keywords: Carbon dioxide; instantaneous transpiration efficiency; ozone exposure; Quercus ilex

Modifications of the leaf surface structures of Quercus ilex L. in open, naturally CO2-enriched environments - Paoletti, E.; Nourrisson, G.; Garrec, J. P.; Raschi, A. (Plant, Cell & Environment, 1998)
Two Italian CO2 springs allowed us to study the long-term effect of a 350–2600 μmol mol–1 increase in CO2 concentrations on the surface structures of leaves of Quercus ilex L. Carbon dioxide increased the quantity of cuticular waxes, above an apparent threshold of 750 μmol mol–1 CO2. Leaf wettability was not modified by CO2 concentrations. Reduction in stomatal frequency was observable up to 750 μmol mol–1 CO2, the slope being almost the same as that estimated for the increase in CO2 concentration from pre-industrial times to the present. At higher concentrations, CO2 seemed to exert no more impact on stomatal frequency.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Elevated CO2; leaf wettability; natural CO2 spring; Quercus ilex; stomatal frequency; wax amount

New type of damage to Quercus ilex: pollen germination and hydration ability - Bellani, Lorenza M.; Paoletti, E. (European Journal of Forest Pathology, 1992)
Pollen grains collected from trees of Quercus ilex L. belonging to different classes of new type damage were analyzed. Five parameters were taken into account: viability, germinability, tube lengthening, grain volume of the dehydrated state and after rehydration. Damage to mother plants clearly influences the above mentioned parameters, causing a reduction in pollen grain viability, germinability, and in the ability of the grains to rehydrate.
Keywords: damage; germination (voyant); pollen; pollution; viability